Examining Open University Malaysia’s learners’ satisfaction with HTML5 package in an ODL environment - Bakar, Shawira Abu; Yasin, Nooni Ezdiani; Zabidi, Nazrai Ahmad (Journal of Education and Learning (EduLearn), 2026)
This study explores the satisfaction levels of Open University Malaysia (OUM) learners with HTML5 package (H5P)-developed interactive content in open and distance learning (ODL). The research objectives include examining learners’ perceptions of H5P-generated content in terms of usability, interactivity, and relevance, and assessing learners’ satisfaction levels with H5P in terms of overall effectiveness and engagement. Despite the extensive research on H5P across various educational contexts, its particular use in ODL remains underexplored. This paper offers an in-depth perspective on how H5P enhances learner experiences in ODL, as well as highlights critical factors that affect learner satisfaction. This will be beneficial for instructional designers and educators who seek to improve engagement within self-instructional materials. The findings indicate that 85% of participants reported higher levels of engagement with H5P content, according to quantitative data. Additionally, according to 80% of students, interactive materials created using H5P enhanced their comprehension of the material. This suggests that H5P holds promise as an effective tool for enhancing learner engagement and satisfaction in ODL contexts. The study contributes to the growing body of literature on technology-enhanced learning by providing insights into the use of interactive content tools like H5P in ODL environments.